Improving esthetics of finger prosthesis by glove silicone - Laxman Singh Kaira; Esha Dabral (Wolters Kluwer Medknow Publications, 2014)
Finger and partial finger amputations are some of the most frequently encountered forms of partial hand loss. A high quality esthetic prosthesis with passive function can be helpful to the patient since loss or congenital absence or malformation have both a social and psychological impact on the patient. Prosthetics is an art and science, which provides lifelike appearance to the lost structures of the patient. This case report presents the fabrication of a silicone finger prosthesis, which had good suspension, adequate function, was comfortable to use and esthetically acceptable to the patient.